Long-term field experiments in the crop production and agroecology - Kismányoky, Tamás (Acta Agraria Debreceniensis, 2018)
In Hungary, there are 57 LTFEs included 13360 plots of them 51 trials elder than 20 years, more than 50 years are 32 trials and 6 less than 20 years old. Compared to the 2003 statistical data, some 26 LTFEs ceased to operate in the course of the last 15 years. All research workers and scientist have to do the best to preserve the recently still existing LTFE’s. This paper presents the list of the currently active LTFEs with some comments including the locations, year of setting and the number of plots.